PERAN MANAJEMEN PENDIDIKAN DALAM PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN SISWA MELALUI PROGRAM TATANEN DI BALE ATIKAN DI SEKOLAH DASAR (Studi Kasus di SD Negeri 1 Sukamanah Kecamatan Bojong Kebupaten Purwakarta) - Warta, Waska; Iin Iskandar; Sapari, Asep; Dwinanda Kardiwan, Delfi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of educational management in shaping students' environmental care character through the Tatanen di Bale Atikan Program at Sukamanah State Elementary School 1, Bojong District, Purwakarta Regency. Using a qualitative approach and case study method, data were collected through participant observation, in-depth interviews with the school principal, teachers, students, and parents, as well as documentation analysis. The results of the study show that educational management, which includes planning, organizing, implementing, and evaluating (POAC), plays a very significant role in shaping students' environmental care character. Through the Tatanen di Bale Atikan Program, students experienced improvements in knowledge, attitudes, and real behaviors such as maintaining cleanliness, caring for plants, and appreciating the environment. This study concludes that effective educational management based on local wisdom is capable of creating meaningful learning and forming students' environmental care character in a sustainable manner.